Teaching Dilemmas and Solutions in Content-Area Literacy, Grades 6-12 - Smagorinsky, Peter (Corwin, 2014)
This book provides suggestions on how to develop curriculum and instruction that are responsive to students' needs across English/language arts, science, social studies, mathematics, visual space, and music and drama.